Radiation dynamics of sweetpotato (Ipomoea batatas (l.) lam) in response to different cropping systems with a legume crop - I., Nur Arina; Mohammad Yusoff, Martini; M., Azizah; R., Mohd Fauzi; J., Mashitah; M., Farrah Melissa; M. I., Isharuddin (Asian Network for Scientific Information, 2020)
Background and Objective: The production of sweetpotato (Ipomoea batatas L.) in Malaysia is far below the projected yield of approximately 20 t ha-1. Two field studies were conducted to assess the mechanism underlying the interception of photosynthetically active radiation and radiation use efficiency as influenced by different cropping systems on growth performance, tuber yield and phytochemical contents of sweetpotato. Materials and Methods: Four treatments (sole sweetpotato, sole soybean, mixed sweetpotato-soybean and relay sweetpotato-soybean) were arranged in a four repeated Randomized Complete Block Design (RCBD). Results: In Study 1, sweetpotato in mixed system showed higher total dry matter, total crop yield and harvest index than relay system, but reported to be higher than sole system in Study 2. The land equivalent ratio greater than 1 was shown by mixed system in Study 1 and mixed and relay systems in Study 2, which means over yielding occurred and the intercrops were more productive than the sole system. In Study 1, critical leaf area index as achieved by sweetpotato in sole system (4.17 at 96 Days After Sowing (DAS)), mixed system (4.44 at 90 DAS) and relay system (4.85 at 108 DAS), meanwhile, in Study 2, only sweetpotato on sole system (3.92 at 72 DAS) and mixed system (4.14 at 71 DAS) were achieved when radiation interception reached 95%. In addition, the highest levels of lightness, antioxidant activity, total flavonoid and total phenolic contents were found in the mixed system. Conclusion: Mixed intercropping of sweetpotato and soybean could produce high yield through more efficient resource use.